2007
DOI: 10.1111/j.1600-0633.2007.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance in young Allis shad larvae (Alosa alosa L.)

Abstract: Bardonnet A, Jatteau Ph. Salinity tolerance in young Allis shad larvae (Alosa alosa L.).Abstract -Estuarine migration in Allis shad (Alosa alosa) usually does not take place before mid-summer, but exposure to salinity in brackish water may occur earlier as many spawning areas are of necessity located in upper estuarine zones due to the placement of dams. Therefore, Allis shad conservation programmes need to consider the risk of mortality due to the ability of young Allis shad to tolerate salinity. To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…2007). The other shows very good survival of fish from 5–8 days to 27 days posthatching at salinity 10 g·l −1 (Bardonnet & Jatteau 2008). Both studies clearly indicate that allis shad could be found in the upper‐middle estuary younger than 58 days of age, the age at which the first emigrant enters the estuary according to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…2007). The other shows very good survival of fish from 5–8 days to 27 days posthatching at salinity 10 g·l −1 (Bardonnet & Jatteau 2008). Both studies clearly indicate that allis shad could be found in the upper‐middle estuary younger than 58 days of age, the age at which the first emigrant enters the estuary according to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…larvae abundances observed by Esteves and Andrade (2008) in the oligohaline and mesohaline sections of the Guadiana estuary support these results. However, A. fallax larvae presented clear differences in salinities optimum relatively to other Alosa spp., with A. alosa and A. sapidissima larvae optimum closer to 10 g·L −1 (Limburg and Ross, 1995;Bardonnet and Jatteau, 2008). The observed salinity optima differences for larvae growth and survival could result from species specific physiologic development.…”
Section: Discussionmentioning
confidence: 86%
“…Leach and Houde, 1999;Jia et al, 2009) and European Alosa species (e.g. Aprahamian and Aprahamian, 2001;Bardonnet and Jatteau, 2008). Young A. fallax larvae were able to withstand environments with salinities ranging from 0 g·L −1 up to 15 g·L −1 , thriving at 2.5 g·L −1 while being unable to survive at 20 g·L −1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations